(untitled) (Swiss Medical Weekly, 2011)
BACKGROUND: Considerable criticism has lately been raised by the media regarding the quality of Swiss medical expertises. The present investigation was therefore undertaken to assess the professional quality of Swiss medical expertises. The study was part of a market analysis of medical expertises (MGS study). METHODS: A sample of 97 anonymised expertises randomly chosen from a total of 3165, collected in the MGS study over a period of 3 months, were evaluated by an international board of medical experts and reviewers, using a stepwise developed questionnaire. Each expertise was independently evaluated by two experts. Data were then tested for plausibility (obvious errors and misunderstandings). The main outcome was the overall quality rating of the expertise that was graded from 1 (very poor) to 6 (excellent) in analogy to the Swiss school grading system. For analysis and interpretation the grades were divided into sufficient (grades >= 4) and insufficient (grades <4). RESULTS: Overall 19.6% (95% confidence interval: 13.1%; 28.3%) of the expertises were rated to be of insufficient quality. The quality was inversely related to the number of involved medical disciplines, the time relapsed since injury and positively related to the difficulty of the expertise. In addition, expertises in the French and Italian languages were rated superior to those in German. CONCLUSION: Our results confirm recent criticisms that the professional quality of expertises does not suffice. This is hardly acceptable in face of the financial and personal consequences. There is an obvious need for further research using larger samples and for educational programmes on all levels.